Species Radiation of Carabid Beetles (Broscini: Mecodema) in New Zealand - Goldberg, Julia (Public Library of Science, 2014)
New Zealand biodiversity has often been viewed as Gondwanan in origin and age, but it is increasingly apparent from molecular studies that diversification, and in many cases origination of lineages, postdate the break-up of Gondwanaland. Relatively few studies of New Zealand animal species radiations have as yet been reported, and here we consider the species-rich genus of carabid beetles, Mecodema. Constrained stratigraphic information (emergence of the Chatham Islands) and a substitution rate for Coleoptera were separately used to calibrate Bayesian relaxed molecular clock date estimates for diversification of Mecodema. The inferred timings indicate radiation of these beetles no earlier than the mid-Miocene with most divergences being younger, dating to the Plio-Pleistocene. A shallow age for the radiation along with a complex spatial distribution of these taxa involving many instances of sympatry implicates recent ecological speciation rather than a simplistic allopatric model. This emphasises the youthful and dynamic nature of New Zealand evolution that will be further elucidated with detailed ecological and population genetic analyses.